Digital signal processing & hardware implementation in 77 GHz automotive radar SoC - Rangasamy, Sathishkumar (Nanyang Technological University, 2021)
The main aim of this project is to study the usage of a 77 GHz radar based system in an automotive for the purpose of identification and classification of objects in front of the vehicle. An FMCW (Frequency Modulated Continuous-Wave) radar transmits chirp signal whose frequency increases linearly with time. Reflected signal is then mixed with transmitted signal using a mixer to generate IF ((intermediate frequency) signal. IF signal is converted to digital using ADC. Then FFT (Fast Fourier transform) is performed on the digitized samples to determine range, velocity and angle. While CFAR (Constant false alarm rate) algorithms is discussed to determine the targeted object from the cluster of objects. Since it is an ongoing project so this technical paper is limited to the following stages of the project – 1. Radar sensor hardware environment setup for data collection. 2. Analyze captured data in MATLAB to understand and validate. 3. Range estimation based on frequency spectrum 4. FFT and CFAR algorithms techniques for object identification and clustering.